Transactions of the Philological Society, 1891-4 - Philological Society (Great Britain) (Oxford : Published for the Society by B. Blackwell, 1894)
List of members included in most vols.
Some of the longer contributions have special t.-p., some are issued as appendices.
Pt. 3 of Transactions for 1870-72 never published.
Also available via World Wide Web
Vols. for 1917-66. 1 v.; v. [66]-90, 1967-1992. 1 v.
Keywords: Philological Society (Great Britain) -- Periodicals; Philology -- Periodicals